PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BAJU MEREK THE EXECUTIVE PT DELAMI GARMENT INDUSTRIES - Faizani, Risma Devita; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2020)
Business competition in both the domestic and international markets has turned into hyper competition. Companies who want to develop or are least able to survive must be able to provide customers with goods or services of higher value, quality, availability and better services. The point is to maintain sustainable marketing performance (sustainable marketing). The growth of local products is now growing, including clothing, shoes, bags and much more. There are several well-known Indonesian original brands that are still often considered to be imported. One of them is The Executive brand which is the object of research. This study aims to determine the effect of promotion and price on purchasing decisions for The Executive products. This type of research is explanatory research with nonprobability sampling techniques with purposive sampling and accidental sampling methods. Methods of data collection used questionnaires and interviews with a sample of 100 visitors to The Executive Mall Paragon Semarang. Data processing is performed with the help of SPSS ver 18. Testing includes validity, reliability, correlation coefficient, determination coefficient, simple regression, multiple regression, the significance of the T test and F test. The results indicate a significant positive effect of promotion and price on the product purchase decision Executive Promotion and price together have a positive and significant effect on purchasing decisions for The Executive products.